Return to Sports After Arthroscopic Treatment of Rotator Cuff Calcifications in Athletes. Issue 10 (19th October 2016) - Ranalletta, Maximiliano; Rossi, Luciano A.; Sirio, Adrian; Bruchmann, Guillermina; Maignon, Gastón D.; Bongiovanni, Santiago L.
Background: Arthroscopic treatment of calcific deposits of rotator cuff tears has been described with successful results in the general population. However, despite the high frequency of this condition, there is no information in the literature regarding arthroscopic treatment of rotator cuff calcifications in athletes. Purpose: To analyze the time to return to sport, clinical outcomes, and complications of complete arthroscopic removal of intratendinous calcific deposits and repair of the tendon lesion without acromioplasty in athletes. Study Design: Case series; Level of evidence, 4. Methods: This study retrospectively evaluated 24 consecutive patients with a mean age of 36.2 years. The mean follow-up was 59 months (range, 24-108 months). Patients completed a questionnaire focused on the time to return to sport and treatment course. Pre- and postoperative functional assessment was performed using the Constant score and University of California Los Angeles (UCLA) score. Pain was assessed by visual analog scale (VAS). Radiographs and magnetic resonance imaging (MRI) were performed to evaluate the recurrence of calcifications and the indemnity of the supraspinatus tendon repair. Results: Of the 24 patients, 23 (95.8%) were able to return to sports; 91.3% returned to the same level. The mean time to return to play was 5.3 months (range, 3-9 months): 26% of patients (6/23) returned to sports in less than 4 months, 61% (14/24) returned between 4 and 6 months, and 13% (3/24) returned after the sixth month. The mean Constant score increased from 26.9 preoperatively to 89.7 postoperatively ( P < .001), and the UCLA score increased from 17.3 preoperatively to 33.2 postoperatively ( P < .001). Significant improvement was obtained for pain (mean VAS, 8.4 [before surgery] vs 0.6 [after]; P < .001). The overall majority (91.6%) of patients were satisfied with their result. MRI examination at last follow-up (79% of patients) showed no tendon tears. Conclusion: In athletes with calcifying tendinitis of the supraspinatus tendon with failed nonoperative treatment, complete arthroscopic removal of calcific deposits and tendon repair without acromioplasty results in significant pain relief and improvement in functional outcomes. Most patients return to the same level of proficiency regardless of the type of sport and the level of competition before injury, with 91.6% of patients satisfied with their results.